Original paperAssessment of skin microcirculati on by laser Doppler flowmetry in systemic sclerosis patients - Waszczykowska, Arleta; Goś, Roman; Waszczykowska, Elżbieta; Dziankowska-Bartkowiak, Bożena; Jurowski, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: First lesions to occur in the course of systemic sclerosis (SSc) involve microcirculation. Aim: The study involved assessment of the suitability of laser Doppler flowmetry (LDF) in examination of the performance of skin microcirculation in the distal portion of the upper extremity in SSc patients. Material and methods : Overall the study involved 27 patients with systemic sclerosis. The control group comprised age – and gender-matched 27 healthy individuals. All the study subjects underwent microcirculation perfusion measurement at rest (rest flow – RF) as well as microcirculatory flow challenge tests – reactive hyperaemia test (RHT) and thermal stimulation test (TST). Results: The study did not show any differences in the skin microcirculation perfusion at rest between the test group and the control, while reactive hyperaemia test results revealed significantly lower skin microcirculation perfusion values during the cuff inflation in SSc patients, as compared to the controls. In the test group, a lower perfusion value was observed during secondary hyperaemia following cuff release. Comparative analysis of skin microcirculation perfusion changes during the thermal stimulation test revealed a significantly lower change of the perfusion value and longer time of return to the baseline in the test group as compared to the control group. Conclusions : The study performed has shown the suitability of LDF in the assessment of the microangiopathy degree in systemic sclerosis patients. The skin perfusion value in SSc patients should be assessed on the basis of parameters obtained in microcirculation challenge tests.